2020
DOI: 10.3389/fmicb.2020.01995
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenomics Characterization of an Emerging Fungal Pathogen, Fusarium oxysporum f. sp. lycopersici in Greenhouse Tomato Production Systems

Abstract: In recent years, greenhouse-grown tomato ( Solanum lycopersicum ) plants showing vascular wilt and yellowing symptoms have been observed between 2015 and 2018 in North Carolina (NC) and considered as an emerging threat to profitability. In total, 38 putative isolates were collected from symptomatic tomatoes in 12 grower greenhouses and characterized to infer pathogenic and genomic diversity, and mating-type ( MAT ) idiomorphs distribution. Morphology and polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 80 publications
(145 reference statements)
0
4
0
1
Order By: Relevance
“…It is known that the nature and extent of the manifestation of external signs of the disease, especially with complex pathogen damage, are determined by examining the distribution of species composition in the pathocomplex, location of infection, degree of aggressiveness and features of the relationship of pathogens in a particular mycosociety, level of plant resistance, and influence of external environmental factors [ 35 , 47 ]. In this study, it was shown that all identified species can contribute to the pathogenesis of tracheomycosis wilting of pepper plants in the Republic of Crimea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the nature and extent of the manifestation of external signs of the disease, especially with complex pathogen damage, are determined by examining the distribution of species composition in the pathocomplex, location of infection, degree of aggressiveness and features of the relationship of pathogens in a particular mycosociety, level of plant resistance, and influence of external environmental factors [ 35 , 47 ]. In this study, it was shown that all identified species can contribute to the pathogenesis of tracheomycosis wilting of pepper plants in the Republic of Crimea.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of F. oxysporum (FOSC) and F. solani (FSSC), as the main pathogens, to cause symptoms of vascular wilt in plants of the Solonaceae family has also been noted by other scientists in their studies. Recent studies conducted in North Carolina [ 47 ], Mexico [ 48 ], Poland [ 49 ], South Korea [ 50 ], Pakistan [ 29 ], and India [ 15 ] have shown that these two dominant pathogens have remained a serious threat to pepper, tomato, physalis, eggplant, and potato production in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…'Fortamino' (Enza Zaden Salinas, CA) was added in 2018 to gain information on a vigorous and Fusarium oxysporum f. sp. lycopersici race 3 resistant rootstock because of the emergence of race 3 in North Carolina at the time of this study (Adhikari et al, 2020). Non-grafted plants of both scion cultivars were used as controls.…”
Section: Rootstocks and Scionsmentioning
confidence: 99%
“…tomada de: [13] Por otro lado, Fusarium oxysporum (figura 2) es un hongo ampliamente distribuido en suelo y abarca un complejo variable de cepas con características morfológicas y patológicas diferentes, algunas de estas cepas son saprótrofos y endófitos comensales que colonizan la raíces, pero no representan una amenaza para la planta, es más, cepas específicas pueden generar un beneficio para el huésped ocasionando protección ante diferentes patógenos que la pueden afectar, sin embargo, Fusarium oxysporum también presenta un complejo de cepas que permiten categorizarlo como hongo emergente, ya que invaden diferentes tipos de plantas distribuidas en el mundo ocasionando síntomas característicos como clorosis en las hojas, necrosis de los sistemas vasculares o muerte del huésped ya que este coloniza el xilema. [14] [15]…”
Section: Introductionunclassified